Implementasi Pembiayaan Akad Mudharabah di KSPPS BMT TAMZIS BINA UTAMA Cabang Secang Kabupaten Magelang - Fahrudin, Adi; Purwanto; Rifa’i, Fuad Yanuar Akhmad (Forum Kerjasama Pendidikan Tinggi, 2023)
Distribution of financing using a Mudharabah Agreement at KSPPS BMT TAMZIS Bina Utama Secang Branch, Magelang Regency, is the most popular contract with the public. Financing using the Mudharabah contract scheme is carried out to support business development and encourage business actors to increase their business capacity. This research analyzes the implementation and execution of Mudharabah contracts at KSPPS BMT TAMZIS Bina Utama Secang Branch based on DSN MUI Fatwa Number 07/DSN-MUI/IV/2000. This research includes field research with qualitative methods. Research data was obtained through interviews, observation, and documentation. The data that has been collected is then analyzed using interactive analysis techniques. The research results show that the Mudharabah Agreement financing product is the product given to members of KSPPS BMT TAMZIS Bina Utama Secang Branch and all capital at the time of the profit-sharing agreement (nisbah). This financing is specifically designed for members who will develop their business with a profit-sharing scheme so that there is uncertainty in collaboration. This financing is adjusted to members' funding needs with an installment return scheme according to the agreed time period. 2) The implementation of KSPPS Tamzis Bina Utama Secang Branch mudharabah financing is quite good. It follows procedures, competitive profit-sharing calculations, and excellent service to members to provide satisfaction, and its implementation is in line with MUI DSN Fatwa Number: 07/DSN- MUI/IV/2000.